2006
DOI: 10.4314/ajtcam.v3i4.31182
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vivo screening method for the evaluation of new anti helicobacter medicinal preparations

Abstract: The objective of this study was to devise a rapid mouse model for the in vivo screening of new anti Helicobacter pylori products. Six to eight week-old mice pretreated (7 days) with Amoxicillin/Metronidazole (25 mg/kg) to eliminate all Helicobacter-like organisms were inoculated (4x per week) with 200 µl of a bacterial culture (10 8 CFU/ml of H. pylori CCUG-39500). Colonisation of mouse stomach was assessed from day 1 to 15 post inoculation by the Gram stain, rapid urease test and antral mucus culture. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Taking into consideration these data as well as the limitations of in vitro efficacy experimentation, we also evaluated the in vivo eradication potency of HZJW in previously described rapid screening mouse model [20]. In the rapid urease assay, all animals in control group were negative for urease reaction, whereas in H .…”
Section: Resultsmentioning
confidence: 99%
“…Taking into consideration these data as well as the limitations of in vitro efficacy experimentation, we also evaluated the in vivo eradication potency of HZJW in previously described rapid screening mouse model [20]. In the rapid urease assay, all animals in control group were negative for urease reaction, whereas in H .…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical studies have shown that columbamine, jatrorrhizine, palmatine and menisperine are major diterpenoid lactones and alkaloids compounds in Radix Tinosporae [ 33 ]. Although no investigations on antibacterial activity of TSG, columbamine, jatrorrhizine and menisperine against H. pylori have been reported, there are a few reports on palmatine; 16 μg/mL palmatine in vitro or 50 mg/kg in vivo killed H. pylori [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the day following the last administration of the extracts the animals were fasted for 10-12 h, after which they were sacrificed. The stomachs were excised and gastric biopsy samples were taken and used to assess H. pylori clearance by Gram staining, rapid urease test, and culture (Fauchere, 1999;Boda et al, 2006).…”
Section: In Vivo Assessment Of Anti-h Pylori Activity In Infected Micementioning
confidence: 99%